Managing Immigration to Support National Interests: Indonesia's Strategies and Efforts - Prasetyo, Teguh; Nugraha, Prasetya (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: To explore Indonesia's political stance on managing international migration to safeguard national interests, analyse the current immigration policy framework, and formulate strategies for sustainable immigration management using SWOT analysis. Design/Methodology/Approach: A qualitative methodology was adopted, utilising data from the United Nations High Commissioner for Refugees (UNHCR), the International Organization for Migration (IOM), and domestic regulations such as Law No. 6/2011. A SWOT analysis was conducted to evaluate Indonesia's immigration policies. Findings: Indonesia's strategic geographical position offers significant economic advantages. However, current immigration policies remain suboptimal. The SWOT analysis identifies strengths such as strategic location and opportunities through multilateral partnerships. Conversely, weaknesses include inadequate inter-stakeholder coordination, while threats stem from transnational crimes. These issues necessitate preventive strategies, technological advancements, and regulatory reforms to close legal loopholes. Originality/Value: This research offers new insights into immigration management through a multilateral approach, domestic regulatory reforms, and technological optimisation, contributing to national stability and Indonesia's strategic interests sustainably.